ACTIV-5: A Digital Education Strategy for Tuberculosis Prevention in the Community: ACTIV-5: Strategi Edukasi Digital untuk Cegah TBC di Komunitas - Baiq Reny Ermayuningsih; Mar'atus Sholihah; Sri Wahyuni; Tanwirullaily; Nurfika Asmaningrum; Anisah Ardiana; Fatimah (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Tuberculosis remains a serious public health issue in Indonesia. Low public awareness, delayed diagnosis, and poor treatment adherence have worsened the spread of the disease. This community service activity aimed to enhance public understanding of TB prevention through a digital educational video based on the ACTIV-5 strategy, and to evaluate its effectiveness in improving knowledge scores before and after the intervention. The program was conducted from June 30 to July 2, 2025, using a quasi-experimental pretest-posttest design. A total of 172 respondents were purposively selected from a population of 302 individuals. Education was delivered by screening short videos based on the ACTIV-5 strategy in the waiting area of the health center. Respondents’ knowledge was measured using a structured questionnaire administered before and after the intervention. During the educational period, a total of 320 patient visits were recorded. Data were analyzed using basic quantitative methods. Pretest results showed that most respondents lacked understanding of TB symptoms and transmission mechanisms. After the intervention, there was a significant increase in knowledge scores, particularly in recognizing early symptoms and the importance of completing treatment. The average score improved by more than 40% from the baseline. In conclusion, the ACTIV-5-based educational video proved to be effective and holds potential as a sustainable educational strategy in primary healthcare services. It is recommended that the program be replicated in other public health centers to expand its promotive and preventive impact on TB control.